Predatory Pricing in Flash Sale Practices on E-Commerce Media in Review of Competition Law - Junianti, Winda; Munib, Muhammad Abdim (Jurnal Ius Constituendum, 2024)
The purpose of this study is to analyze flash sales related to predatory pricing activities prohibited by the Business Competition Law and to explain law enforcement related to predatory pricing activities. A flash sale can be said to be predatory pricing if it meets the elements in Law No. 5 of 1999, Article 20. In this study, the author uses normative legal research methods using an approach to law and a conceptual approach to the problem of whether flash sales are related to predatory pricing activities and how predatory pricing law enforcement is reviewed in business competition law. This paper provides a conceptual view as stated in the Business Competition Law as well as the implementation of the law. The results and discussion of the formulation are that flash sale activities are not related to predatory pricing activities because flash sales do not meet the elements of selling and loss activities, and enforcement of predatory pricing laws in business law is to provide criminal penalties and administrative penalties in accordance with the provisions of Law No. 5 concerning the Prohibition of Monopoly Practices and Unfair Business Competition.